Dietary iodine and selenium intake by participants older people at the University of the Third age - Vicentini, Geraldo Emílio; de Paula, Milena Baggio; Calixto, Maria Rachel Pedrazzoli; Ferreto, Lirane Elize Defante (Disciplinarum Scientia | Saúde, 2023)
This study aimed to evaluate the dietary intake profile of iodine and selenium in participants of the University of the Third Age (UNATI). This cross-sectional study estimated dietary intake using a food frequency questionnaire administered to 30 participants. The mean age was 67.6 years, the majority were women (90%), and 83.3% were older than 60 years. The mean iodine intake was estimated to be 198.9 ± 50.8 µg/day, and selenium intake was 369.9 ± 145.3 µg/day, both above the recommended dietary intakes. Two categories were created based on the median (50th percentile), one category ≤ 68 years and the other > 68 years. The mean intake between the two categories was not significantly different for iodine (p=0.467) and selenium (p=0.146). The category > 68 years consumed more dairy products (p=0.045) and vegetables (p=0.039) than the younger category. Daily intake of iodine and selenium showed no correlation with each other (r=0.134; p=0.480) or with age (iodine: r=-0.199; p=0.289; selenium: r=0.150; p=0.429). Total iodine intake was positively correlated with salt (p<0.001), dairy products (p=0.016), and vegetables (p=0.018). Selenium intake was positively associated with eggs, meat, and fish (p<0.001) and nuts and legumes (p<0.001). Iodine intake was adequate for almost the entire group, with no excess consumption. No deficiency was observed concerning selenium intake, and intake was either sufficient or excessive without posing a disease risk.